2017
DOI: 10.1088/1361-6455/aa5996
|View full text |Cite
|
Sign up to set email alerts
|

Potential splitting approach to e–H and e–He+scattering

Abstract: An approach based on splitting the reaction potential into a finite range part and a long range tail part to describe few-body scattering in the case of a Coulombic interaction is proposed. The solution to the Schrödinger equation for the long range tail of the reaction potential is used as an incoming wave. This reformulation of the scattering problem into an inhomogeneous Schrödinger equation with asymptotic outgoing waves makes it suitable for solving with the exterior complex scaling technique. The validit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…The terms [A R 1 ] n, andà n, correspond to the functions Ψ R 1 and Φ = Φ 0 + Φ 1 , respectively. Projecting the representation (5) on the two body wave functions, the local representation for the partial amplitudesà n, can be derived [6]:…”
Section: Theoretical Approachmentioning
confidence: 99%
See 1 more Smart Citation
“…The terms [A R 1 ] n, andà n, correspond to the functions Ψ R 1 and Φ = Φ 0 + Φ 1 , respectively. Projecting the representation (5) on the two body wave functions, the local representation for the partial amplitudesà n, can be derived [6]:…”
Section: Theoretical Approachmentioning
confidence: 99%
“…In several recent studies, we have reported a method which is capable to treat correctly the Coulomb scattering problem using exterior complex scaling [3][4][5][6]. The key point of this method is splitting the long-range Coulomb potential into the core and tail parts.…”
Section: Introductionmentioning
confidence: 99%
“…Even though the basic mathematical model for such a broad spectrum of physical systems is the Schrödinger equation, the diversity of model interactions and particular physical states leads to a variety of employed computational methods [12][13][14][15][16][17][18][19][20][21][22][23][24][25]. Thus, our ability to perform direct model-free calculations for such wide range of systems is of utmost importance for many branches of physics.…”
Section: Introductionmentioning
confidence: 99%
“…Even though the basic mathematical model for such a broad spectrum of physical systems is the Schrödinger equation, the diversity of model interactions and particular physical states leads to a variety of employed computational methods [12,13,14,15,16,17,18,19,20,21,22,23,24,25]. Thus, our ability to perform direct model-free calculations for such wide range of systems is of utmost importance for many branches of physics.…”
Section: Introductionmentioning
confidence: 99%